SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT DAN HAMA PADA TANAMAN SALAK DI TURI SLEMAN - Honggowibowo, Anton Setiawan; Pujiastuti, Asih; Susanti, Linda Putri (Compiler, 2017)
Expert systems are systems that adopt human knowledge into computers designed to solve problems like an expert. Salak plants, especially in TuriSleman Yogyakarta area has several obstacles such as diseases and pests in salak plants which is a problem for salak farmers. Expert research Expert system to diagnose diseases and pests in this salak crop helps salak farmers overcome the problems of disease and pests. Salak farmers only need to enter the symptoms experienced in the barking plants later data will be processed symptoms entered by the system. This application performs checks with the system as consulted with a salak plant experts to find out the diseases and pests that attack on the barking plants and find solutions. Implementation in this application using TOPSIS method, TOPSIS method yields the highest rank value for the final result value. This application takes data and performs testing in UPT BP4 Region V Sleman with Turi OPT (Plant-disturbing organisms) officer.